Efforts to Facilitate the Development of Adolescent Sexuality through Training for Counseling Teachers - Jane Savitri; Marissa Chitra Sulastra; Sharon Charish Abigail Wigoeno; Christine Widiapradja (Journal of Innovation and Community Engagement, 2023)
Today, sex education for teenagers has become increasingly important. Adolescents experience a sexual crisis with various sexual problems they experience, such as pornography, pornoaction, masturbation, confusion of sexual orientation, free sex behavior, sexual violence, and sexual harassment. This phenomenon has attracted the attention of teachers, especially counseling teachers at SMP BPK Penabur Jakarta to assist students in developing healthy sexual development. When teachers can understand adolescent sexuality and have the skills to provide appropriate psychoeducation about sex education to students, they will be more competent to apply it to prevent and intervene in student problems, especially in sexual matters. By using the survey method and descriptive analysis, the evaluation results showed a positive response from the counseling guidance teachers to be able to carry out the training. In addition, the evaluation results show that teachers acquire knowledge and skills about psychoeducation to facilitate healthy sexual development among students. This psychoeducation can be developed for a wider context.